Kendala Guru Dalam Memberikan Penilaian Sikap Siswa Kelas 1 Dalam Proses Pembelajaran Berdasarkan Kurikulum Merdeka - Fatimah Zahra; Dalila Pohan; Rahma Aulia; Syahrial Syahrial (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research was conducted with the aim of obtaining information regarding teacher’s obstacles in providing assessments of grade 1 elementary school students during the independent curriculum learning process at Pelangi Elementary School in Medan. The structure used by researchers in this research is a qualitative approach and using descriptive methods. This qualitative approach is used to be able to define, formulate and dig deeper into everything related to this research. The results of this research prove that the obstacle for teachers in assessing students’ readiness for the learning process is that teacher have difficulty in overcoming students’ politeness, discipline and cooperation. To overcome obstacles in assessing attitudes in independent curriculum learning, teacjer hold discussion activites with other teachers and collaborate with students’ parents